Supporting patient and public partners in writing lay summaries of scientific evidence in healthcare: a scoping review protocol. Issue 12 (14th December 2022) - Zarshenas, Sareh; Mosel, JoAnne; Chui, Adora; Seaton, Samantha; Singh, Hardeep; Moroz, Sandra; Khan, Tayaba; Colquhoun, Heather
Abstract : Introduction: Despite growing interest among patient and public partners to engage in writing lay summaries, evidence is scarce regarding the availability of resources to support them. This protocol describes the process of conducting a scoping review to: (1) summarise the source, criteria and characteristics, content, format, intended target audience, patient and public involvement in preparing guidance and development processes in the available guidance for writing lay summaries; (2) contextualise the available guidance to the needs/preferences of patient and public partners and (3) create a patient and public partner-informed output to support their engagement in writing lay summaries. Method and analysis: A scoping review with an integrated knowledge translation approach will be used to ensure the collaboration between patient/public partners and researchers in all steps of the review. To meet objective 1, the English language evidence within a healthcare context that provides guidance for writing lay summaries will be searched in peer-reviewed publications and grey literature. All screening and extraction steps will be performed independently by two reviewers. Extracted data will be organised by adapting the European Union's principles for summaries of clinical trials for laypersons. For objectives 2 and 3, a consultation exercise will be held with patient and public partners to review and contextualise the findings from objective 1. A directed content analysis will be used to organise the data to the needs of the public audience. Output development will follow based on the results. Ethics and dissemination: Ethics approval will be obtained for the consultation exercise. Our target audience will be stakeholders who engage or are interested in writing lay summaries. Our dissemination products will include a manuscript, a lay summary and an output to support patient and public partners with writing lay summaries. Findings will be published in a peer-reviewed journal and presented at relevant conferences. Open science framework registration: osf.io/2dvfg .